Barriers of dietary salt reduction among hypertensive patients: a cross sectional study - Khwaja, Mariyam (International Journal Of Community Medicine And Public Health, 2020)
Background: Healthy dietary practice is an important lifestyle modification and one of the key adjuncts to pharmacotherapy in management of hypertension. A modest reduction in salt intake of 5 gm/day lowered blood pressure by 7/4 mmHg diastolic in hypertensive patients. Despite knowledge about the ill consequences, many people continue to consume high levels of salt in their diet. To motivate people to reduce salt in their diet, a solid understanding of barriers encountered by those under salt reduction recommendation is necessary. Hence, this study was conducted with the aim of identifying the barriers to dietary salt reduction among hypertensive patients. Methods: A community based cross sectional study was conducted on a sample of 356 hypertensive patients in field practice areas (urban and rural) in Department of Community Medicine, JNMC, AMU, Aligarh. A pretested semi-structured questionnaire was used for the study. Compliance to dietary salt intake was assessed by calculating average salt intake per person per day. The tenets of health belief model were used to examine the key determinants of human behavior. Analysis was done by using correlation, proportions, chi-square and multiple linear regression. Results: 31.4% of the participants took salt <5 gm per day. A significant association was noticed with area, religion, social class, family size, perceived benefits and perceived susceptibility. A significant positive correlation was seen with total adherence score and family size. Conclusions: A lot of barriers hinder the compliance to dietary salt reduction. Health Education stressing the role of salt reduction in control of blood pressure is recommended.